2012
DOI: 10.1038/ctg.2012.17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Notch and TGF-β Signaling Expression in Different Stages of Disease Progression During Hepatitis B Virus Infection

Abstract: OBJECTIVES:CD4+ regulatory T cells (Tregs) seem to have a key role in persistence of hepatitis B virus (HBV) infection. Notch and transforming growth factor (TGF-β) signaling independently help in the differentiation and regulation of CD4+T cells, including T-helper (TH) 1, TH2, and Tregs. Whether, the two pathways have modulatory role on different stages of HBV infection and severity of liver disease is not clear. We investigated Notch and TGF-β families' gene expression in peripheral blood and intrahepatic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Notch3 and Notch4 are not expressed in normal liver [50, 112] but Notch4 is expressed by hepatocytes at the edge of regenerative nodules and in cell planes adjacent to fibrous septa [112], While Notch3 is significantly up-regulated in fibrotic liver tissues from patients with chronic active hepatitis [50]. Expression of Notch1 and Hes1 is reduced in activated hepatic stellate cells (HSCs) [9] but hepatitis B virus (HBV) infection drives increased Notch1 expression in intrahepatic T cells in cirrhosis [113]. Notch 2, Notch 3, Hey2 and HeyL expression increases significantly during activation of quiescent HSCs to myofibroblastic HSCs [49].…”
Section: Notch and Liver Fibrosismentioning
confidence: 99%
“…Notch3 and Notch4 are not expressed in normal liver [50, 112] but Notch4 is expressed by hepatocytes at the edge of regenerative nodules and in cell planes adjacent to fibrous septa [112], While Notch3 is significantly up-regulated in fibrotic liver tissues from patients with chronic active hepatitis [50]. Expression of Notch1 and Hes1 is reduced in activated hepatic stellate cells (HSCs) [9] but hepatitis B virus (HBV) infection drives increased Notch1 expression in intrahepatic T cells in cirrhosis [113]. Notch 2, Notch 3, Hey2 and HeyL expression increases significantly during activation of quiescent HSCs to myofibroblastic HSCs [49].…”
Section: Notch and Liver Fibrosismentioning
confidence: 99%
“…Reports of chronic inflammation in autoimmune disorders such as rheumatoid arthritis suggest that increased infiltration of Foxp3+Tregs in damaged organs and at the sites of inflammation has a suppressive role in combating injurious inflammation [26]. In nonautoimmune diseases such as chronic viral hepatitis and primary biliary cirrhosis, studies have suggested that Tregs are involved in the maintenance of chronic inflammation [27,28]. In support of the latter finding, recent work from our group has indicated a role for Tregs coupled to activation of Notch and TGF-β in perpetuation of the inflammatory response during liver disease progression in cirrhosis and HCC in chronically hepatitis B virus (HBV)-infected patients [27] (fig.…”
Section: Inflammatory Bed Inflammasomes and Regenerating Nodules Durmentioning
confidence: 99%
“…4 Graphical representation showing Notch/TGF-β signaling and T cell activation during liver disease progression through phases of acute and chronic HBV infection with respect to the later stages of end-stage liver disease, i.e., cirrhosis and HCC. Activation is seen during the acute and end stages of liver disease, whereas attenuation is noted during the chronic stage of infection [28]. …”
Section: Inflammatory Bed Inflammasomes and Regenerating Nodules Durmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a panel of miRNAs could be used to identify the immunological status of patients. From the above identified miRNA target genes the majority have been described as regulators or suppressors of carcinogenesis or HBV replication [174,175,176,177,178]. This, once more, highlights the role of microRNA during the course of infection and liver damage; however, further studies are required to clarify the mechanisms involved.…”
Section: Circulatory Mirnas As Biomarkers In Paediatric Liver Diseasementioning
confidence: 99%